Patty hits the court : game day!. - "Mills, Patty" (A & U Children: Sydney, 2017)
A fantastic and fun basketball series by Australian Olympian and NBA star Patty Mills that will entertain young readers, inspire kids to achieve their goals through sport, and showcase Patty's pride in his Indigenous heritage
Keywords: Classic fiction